2014
DOI: 10.5007/1984-8412.2014v11n3p261
|View full text |Cite
|
Sign up to set email alerts
|

Os efeitos do bilinguismo e do multilinguismo nas funções executivas

Abstract: RESUMO: Pesquisas têm constatado que bilíngues e multilíngues tem desempenho superior em comparação com monolíngues em tarefas não linguísticas que envolvem processamento executivo. Contudo, os estudos sobre vantagem bilíngue ou multilíngue em tarefas linguísticas são mais escassos, e os resultados, menos consensuais. No Brasil, os benefícios das funções executivas no bilinguismo não têm sido consistentemente identificados nas populações bilíngues, sobretudo nos falantes da língua minoritária Hunsrückisch (uma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…Bilingual advantages in executive function (henceforth EF) have been reported in bilingual children (Poulin-Dubois et al 2011), young adults (Pelham & Abrams 2014), and older adults (Bialystok et al 2004) (for a review, see Valian 2015). Similarly, studies have shown an advantage in multilingual adults when compared to monolinguals (Limberger & Buchweitz 2014). More interestingly, while multilingual adults were found to be less likely to develop cognitive impairments than bilinguals (Perquin et al 2013), studies on the multilingual executive function advantage have found no difference between bilingual and multilingual children (Schroeder & Marian 2017).…”
Section: Bilingualism and Executive Functionsmentioning
confidence: 99%
“…Bilingual advantages in executive function (henceforth EF) have been reported in bilingual children (Poulin-Dubois et al 2011), young adults (Pelham & Abrams 2014), and older adults (Bialystok et al 2004) (for a review, see Valian 2015). Similarly, studies have shown an advantage in multilingual adults when compared to monolinguals (Limberger & Buchweitz 2014). More interestingly, while multilingual adults were found to be less likely to develop cognitive impairments than bilinguals (Perquin et al 2013), studies on the multilingual executive function advantage have found no difference between bilingual and multilingual children (Schroeder & Marian 2017).…”
Section: Bilingualism and Executive Functionsmentioning
confidence: 99%
“…Monolingualism refers to only knowing and using one language (Raitskaya & Tikhonova, 2023). Bilinguals speak two languages, and multilinguals are proficient in three or more languages, focusing on the third language learned (Limberger & Buchweitz, 2014). This may imply that multilingualism is a broader term that includes the concept of bilingualism (Aronin & Hufeisen, 2009;DEWAELE et al, 2024;Raitskaya & Tikhonova, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, researchers now recognize the unique nature of acquiring a third language and its impact on cognition. Third-language learners benefit from increased language exposure and develop better learning strategies and metalinguistic awareness (Limberger & Buchweitz, 2014). Multilingual adults exhibit distinct brain functional connections, particularly in emotional tasks and at rest, and demonstrate strong correlations between working memory connectivity and behavioral performance (Kwon et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, all of our participants speak Standard German, which they might have been using for decoding the unfamiliar dialect. It would be fascinating to conduct similar experiments in Brazil with participants who speak Rio Grande Hunsrückisch (LIMBERGER, 2018;LIMBERGER;BUCHWEITZ, 2014). This population would enable us to include groups with and without formal schooling in German.…”
Section: Bernardo K Limberger and Augusto Buchweitz -One Of The Linesmentioning
confidence: 99%